Automatic assessment methods of A pilot's flight in the traffic circuit. Issue 2 (2nd April 2016) - Masiulionis, Tadas
Abstract: With an increasing number of aircraft, navigation requirements and fast development of avionics systems, as well as the need for the integration of UAVs into airspace, pilots are facing new challenges that need to be mitigated by the development of additional training and assessment systems. These measures would both assess and encourage student pilots to improve their performance by using predetermined flight accuracy requirements based on established flight corridors. In this paper, automatic assessment methods to be used for pilot flight assessment while flying in the circuit are analysed.